On the application of hollow conductor as electrical earthing electrode - Siow, Chun Lim; Tuan Mohamad, Tuan Haziq Arif; Gomes, Chandima; Wan Ahmad, Wan Fatinhamamah (Universiti Tun Hussein Onn Malaysia, 2022)
Earthing is essential for electrical installations to safeguard safety of humans and electrical equipment. Vertically driven solid copper electrode is a widely practiced earthing method due to its simplicity and cost effectiveness. With the rising price of copper, the need for cost optimisation is imperative. In this project, hollow copper electrode is being experimented as an earthing electrode. Solid copper electrode is used as reference and vertically driven side by side with hollow copper electrode at two sites with uniform yet contrasting soil resistivity. Earth resistance of both setups was measured regularly using Fall of Potential method. It was found that the earth resistance of hollow copper electrode is tend to be lower than solid copper electrode. This preliminary finding suggests that a more effective earthing system can be achieved with less material and further studies with prolonged period of measurement is required to ascertain the initial conclusion drawn and presented in this paper